Oxytocin activates NF-κB-mediated inflammatory pathways in human gestational tissues. (5th March 2015) - Kim, Sung Hye; MacIntyre, David A.; Firmino Da Silva, Maria; Blanks, Andrew M.; Lee, Yun S.; Thornton, Steven; Bennett, Phillip R.; Terzidou, Vasso
Highlights: In human gestational tissues OT activates NF-κB via the canonical pathway. OT increases expression of NF-κB mediated inflammatory labour-associated genes. Cross-talk exists between the activation of MAPKs and NF-κB signalling cascades in human amnion. Abstract: Human labour, both at term and preterm, is preceded by NF-κB-mediated inflammatory activation within the uterus, leading to myometrial activation, fetal membrane remodelling and cervical ripening. The stimuli triggering inflammatory activation in normal human parturition are not fully understood. We show that the neurohypophyseal peptide, oxytocin (OT), activates NF-κB and stimulates downstream inflammatory pathways in human gestational tissues. OT stimulation (1 pM–100 nM) specifically via its receptor (OTR) in human myometrial and amnion primary cells led to MAPK and NF-κB activation within 15 min and maximal p65-subunit nuclear translocation within 30 min. Both in human myometrium and amnion, OT-induced activation of the canonical NF-κB pathway upregulated key inflammatory labour-associated genes including IL-8, CCL5, IL-6 and COX-2. IKKβ inhibition (TPCA1; 10 µM) suppressed OT-induced NF-κB-p65 phosphorylation, whereas p65-siRNA knockdown reduced basal and OT-induced COX-2 levels in myometrium and amnion. In both gestational tissues, MEK1/2 (U0126; 10 µM) or p38 inhibition (SB203580; 10 µM) suppressed OT-induced COX-2 expression, but OT-induced p65-phosphorylation was only inhibited in amnion, suggesting OT activation of NF-κB in amnion is MAPK-dependent. Our data provide new insight into the OT/OTR system in human parturition and suggest that its therapeutic modulation could be a strategy for regulating both contractile and inflammatory pathways in the clinical context of term/preterm labour.